Karl Marx - Korsch, Karl, 1886-1961 (Historical materialism book series ;, 2016)
The republication of Karl Korsch's Karl Marx (1938) makes available to a new generation of readers the most concise account of Karl Marx's thought by one of the major figures of twentieth-century Western Marxism. Originally written for publication in a series on 'Modern Sociologists', Korsch's book sought to bring Marx's work to life for an audience of non-specialist readers. As Michael Buckmiller writes in his new introduction to the work, Korsch wanted his book to serve as a passport into the non-dogmatic sections of the American labour movement. The result is a bracing, concise, and accessible overview of the entirety of Marx's thought, and a pungent history of 'Marxism' itself.